Implementasi SIEM dan IDS Dalam Monitoring Terhadap Ancaman Serangan Pada WEB Server - Moh Sulthan Arief Rahmatullah; Andyana Muhandhatul Nabila; Salmaa Satifha Dewi; Vira Datry; Fathika Afrine Azaruddin (STIKes Ibnu Sina Ajibarang, 2024)
Information security and data integration are important aspects in managing and maintaining the continuity of web server system operations. The threat of an attack on a web server can have a serious impact on an organization. This is because websites are able to display text, graphic and sound information from anywhere via the internet network. Behind this convenience, there is a risk of cyber security threats in the use of internet-based technology because it can be accessed from anywhere and by anyone who wants to steal sensitive information or take over the system. In this research, the way to overcome this problem is through implementing a SIEM security information system with the wazuh/Teler platform as an IDS which will be installed on the web server to visualize logs and detect threats to network traffic, especially those leading to the web server. The method used in this research is documentation and forensic investigation in researching or analyzing server log data on websites using wazuh and teler.